Handle-attachments from nubia. A note - Culican, William (Zephyrvs, 2009)
Information on the distinctive bronze handle - attachments in the shape of a pair of human hands has been painstakingly collected by Dr. E. Cuadrado in his Refertorio de los Recipientes Rituales metálicos con "Asas de Manos" de la Península Ibérica (Trabajos de Prehistoria XXI, Madrid 1966). There is little room to doubt that metal vessels with this form of handle, whether we regard them as braziers (braserillos in the older terminology) or 'ritual vessels' as does Cuadrado, are related to the distribution of Phoenician or Punic trade and influence in the Iberian peninsula. The southerly 'Tartessian' distribution speaks for itself; for the western 'Levantine' distribution (from Murcia, Alicante, Valencia, Teruel, Tarragona, Málaga, Ibiza) we can postulate Ibiza, Málaga or Cartagena as a probable distribution centre. The examples in the west central meseta (Sanchorreja, El Berrueco, La Osera) come as no surprise in view of the fact that such obviously Phoenician objects as the Sanchorreja belt-buckle, the Berrueco bronzes reached the regions of Avila and Salamanca respectively. Even for the outlying spot on the hand-handle distribution map at Santa Olaya, the cèltic oppidum at the mouth of the River Mondego, a context of Phoenician trade is likely, since pottery of Carmona and later types was found there and is now in the museum at Figueira da Foz.